Effects of PCSK9 inhibition on glucose metabolism and β-cell function in humans: a pilot study - Moffa, Simona; Mezza, Teresa; Ferraro, Pietro Manuel; Di Giuseppe, Gianfranco; Cefalo, Chiara M. A.; Cinti, Francesca; Impronta, Flavia; Capece, Umberto; Ciccarelli, Gea; Mari, Andrea; Pontecorvi, Alfredo; Giaccari, Andrea (Frontiers in Endocrinology, 2023)
Background Anti-PCSK9 monoclonal antibodies are effective in reducing LDL-C and cardiovascular events by neutralizing circulating PCSK9. PCSK9, however, is also expressed in tissues, including the pancreas, and studies on PCSK9 KO mice have shown impaired insulin secretion. Statin treatment is already known to affect insulin secretion. Our aim was to conduct a pilot study to evaluate the effect of anti-PCSK9 mAb on glucose metabolism and β-cell function in humans. Methods Fifteen non-diabetic subjects, candidates for anti-PCSK9 mAb therapy, were enrolled. All underwent OGTT at baseline and after 6 months of therapy. During OGTT, insulin secretion parameters were derived from C-peptide by deconvolution (β cell glucose sensitivity). Surrogate insulin sensitivity indices were also obtained from OGTT (Matsuda). Results Glucose levels during OGTT were unchanged after 6 months of anti-PCSK9 mAb treatment, as well as insulin and C-peptide levels. The Matsuda index remained unchanged, while β-cell glucose sensitivity improved post-therapy (before: 85.3±65.4; after: 118.6±70.9 pmol min-1m-2mM-1; p<0.05). Using linear regression, we found a significant correlation between βCGS changes and BMI (p=0.004). Thus, we compared subjects with values above and below the median (27.6 kg/m2) and found that those with higher BMI had a greater increase in βCGS after therapy (before: 85.37±24.73; after: 118.62±26.83 pmol min-1m-2mM-1; p=0.007). There was also a significant correlation between βCGS change and Matsuda index through linear regression (p=0.04), so we analyzed subjects who had values above and below the median (3.8). This subgroup analysis showed a slight though not significant improvement in βCGS in more insulin resistant patients, (before: 131.4±69.8; after: 170.8±92.7 pmol min-1m-2mM-1; p=0.066). Conclusions Our pilot study demonstrates that six-month treatment with anti-PCSK9 mAb improves β-cell function, and does not alter glucose tolerance. This improvement is more evident in patients with greater insulin-resistance (low Matsuda) and higher BMI.